Persepsi Kepala SMK terhadap Topik Materi Pelatihan Intrapreneur - Husaini Usman (Universitas Negeri Malang, 2016)
The pros side says that, in order to increase the skill, training is needed. On the other hand, the contras side states that, although the training has been planned sophisticatedly, the implementation still employs conventional ways. This article presents four research findings, including topics of intrapreneurship material as an important component of the training quality. By sufficient intrapreneur skill, the managerial gap between school managerial and both businessman and entrepreneur hopefully can be reduced. Four issues discussed are the validity and reliability of intrapreneurship material topics, the present picture of training material for principal candidate, and the description of training model for principal candidate